Patients With Ischemic Core ≥70 ml Within 6 h of Symptom Onset May Still Benefit From Endovascular Treatment - Chen, Zhicai; Zhang, Ruiting; Zhou, Ying; Gong, Xiaoxian; Zhang, Meixia; Shi, Feina; Yu, Xinfeng; Lou, Min (Frontiers in Neurology, 2018)
Abstract Background— Large core is associated with poor outcome in acute ischemic stroke (AIS) patients. It is unclear whether endovascular treatment (EVT) could bring benefits to patients with core volume ≥70mL before treatment. We aimed to compare the impact of EVT with intravenous thrombolysis (IVT) on the outcome in patients with core volume ≥70 mL. Methods— We included consecutive anterior circulation AIS patients who underwent MR or CT perfusion within 6 hours post stroke onset, which revealed a core ≥70mL before reperfusion therapy. Good outcome was defined by modified Rankin Scale of 0 to 2 at 90-day. Reperfusion was defined as a reduction in hypoperfusion volume of ≥70% between baseline and 24-hour. Results—104 patients were included. Among them, 76 received IVT only, and 28 received EVT. After adjusting for age, NIHSS score, baseline core volume and onset to imaging time, patients in EVT group were more likely to achieve good outcome compared to IVT patients (OR, 3.875; 95% Cl 1.068-14.055, p = 0.039). More patients in EVT group achieved recanalization (84.0% vs 58.5%, p = 0.027) and reperfusion (66.7% vs 33.3%, p = 0.010) than in IVT group. Reperfusion also independently predicted good outcome (OR, 7.718; 95% Cl 1.713-34.772, p = 0.008). All patients with good outcome achieved recanalization at 24-hour. Conclusions— Our data indicated that patients with core volume ≥70 mL might still benefit from EVT, which was related to its high reperfusion rate.